Sex-Based Disparities in Chronic Myeloid Leukemia: Insights from ASXL1 Mutations and Epidemiological Data - Askar, Rabab Ajmi; Sahib, Hussein A (Central Asian Journal of Medical and Natural Science, 2025)
Chronic Myeloid Leukemia (CML) is a hematological tumor considered through the BCR-ABL1 fusion gene, instigating unrestrained growth of myeloid cells. Whereas Tyrosine Kinase Inhibitors (TKIs) have transformed CML management, differences in sickness proportions and results between sexes requirement additional training. This paper associations perceptions as of a new thesis on ASXL1 mutations and BCR-ABL1 transcript kinds in CML sick, along with wider epidemiological documents, to inspect sex-based alterations in CML vulnerability and advancement. Investigation consistently shows a higher incidence of CML in men compared to women, proposing that men might have a larger innate danger or a larger pool of objective cells susceptible to leukemic alteration. Moreover, research indicate that men with CML often have additional somatic mutations, comprising those in ASXL1, which stay related to worse medical results and sickness development. This evaluation accentuates the serious requirement for sex-disaggregated documents in CML investigation to uncover fundamental biological apparatuses, for example genetic and hormonal aspects, and to progress additional exact, sex-specific management. Accepting these changes is important for progressing personalized medication in CML.